O processo de seleção em bibliotecas universitárias: algumas considerações - ABREU, Josilene de Lima (2017)
It presents a study about the process of Development of Collections in University Libraries, focusing on the selection stage. It discusses about University Libraries, exhibits on the activity of Collection Development and how it contributes to the progress of the collection, and describes how the process of selecting the collection of a University Library, highlighting its criteria and sources that help this selection. Objective is to approach and identify the importance of the process of selection of the collection in University Libraries. Approach used to survey the research was the exploratory research through a bibliographical survey to subsidize the research, a documentary analysis of documents and articles on university libraries and the process of collection selection. It was concluded that well-developed collections directly influence the usability of the library. Therefore, the University Library should direct its collection with a view to accompany the teaching, research and extension activities of the University and, consequently, a strong accompaniment of the professional librarian in the selection process. This is the duty of selecting informational material that supposes the real informational need of the user.